THE EFFECT OF THE DISJUNCTION FEATURES ON ACADEMIC PRODUCT (DEPT. OF ARCHITECTURE, UOD AS A CASE STUDY) - ABDULRAHMAN, BASNA NORI; SANJARY, HASAN ABDULRAZZAQ AL (Journal of Duhok University, 2023)
In the context of architectural design, disjunction is considered a strategy for defining and distinguishing between inside and outside architectural forms. This study focuses on the role of disjunction in architectural education, and the motivation behind this choice is the observation the academic literature has not defined a precise and clear measure for evaluating the degree of disjunction between inside and outside architectural forms and how it affects academic outcomes. The goal of this research is to determine the path of disjunction for architectural engineering students at Duhok University, the types used, and to achieve this, a combination of quantitative and qualitative methods were used, supplemented by computer software as a tool for measuring the degree of disjunction. The research results reveal a descending path in how students deal with disjunction. This path begins in the second stage of their academic journey achieving the highest level of disjunction and gradually declining as they progress. An interesting finding is the direct relationship between the degree of disjunction and its types.